(untitled) - Cross, Gillian (Đồng Nai, 2009)
The victim of a kidnapping, Tug battles fear and brainwashing in this stylishly written thriller. Ages 12-up.
Keywords: English language,Adventures,Ngôn ngữ tiếng Anh,Phiêu lưu mạo hiểm; Readers,Người thích đọc sách